2022
DOI: 10.3389/frvir.2021.751735
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Virtual Reality Technology on Pain and Anxiety in Pediatric Burn Patients: A Systematic Review and Meta-Analysis

Abstract: Introduction: Virtual reality (VR) has the potential to lessen pain and anxiety experienced by pediatric patients undergoing burn wound care procedures. Population-specific variables require novel technological application and thus, a systematic review among studies on its impact is warranted.Objective: The objective of this review was to evaluate the effectiveness of VR on pain in children with burn injuries undergoing wound care procedures.Methods: A systematic literature review was performed using PubMed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
(88 reference statements)
0
12
0
10
Order By: Relevance
“… 35 Niki et al 25 helped end-stage patients realise their wish of ‘going to an unforgettable place’ or ‘going home’ through VR technology, which not only improved the burden of patients’ symptoms but also met their needs, to improve the patient’s symptom burden while meeting the patient’s needs. At present, with the continuous development of science and technology, VR is increasingly applied to patients with cancer, 36 burn patients, 37 clinical teaching, 38 etc, providing a new way of thinking for the symptom management of end-stage patients. The feasibility of VR application in symptom management of end-stage patients has been confirmed, 24 39 and more and more new evidence has emerged.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Niki et al 25 helped end-stage patients realise their wish of ‘going to an unforgettable place’ or ‘going home’ through VR technology, which not only improved the burden of patients’ symptoms but also met their needs, to improve the patient’s symptom burden while meeting the patient’s needs. At present, with the continuous development of science and technology, VR is increasingly applied to patients with cancer, 36 burn patients, 37 clinical teaching, 38 etc, providing a new way of thinking for the symptom management of end-stage patients. The feasibility of VR application in symptom management of end-stage patients has been confirmed, 24 39 and more and more new evidence has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…30,32 Previous systematic reviews and meta-analyses that have evaluated the effectiveness of technologybased interventions for pain management among neonates and children have focused on pediatric patients between the ages of 0 and 21 years. [23][24][25][26][27] Of these reviews, neonates were included only in the work of Ueki et al, 24 where one of the included randomized controlled studies evaluated the effectiveness of vibratory stimulation for alleviating heel stick-associated pain among neonates. The use of technology is becoming increasingly prevalent in neonatal care 33,34 and pain management, 35 and there are indications in the literature that virtual reality is also being used for pain management in newborns.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 There is also evidence that virtual reality distraction is effective at relieving pain among children. Previous systematic reviews and meta-analyses have found that virtual reality interventions can relieve pain in pediatric burn patients, 26 as well as pain associated with needle-related procedures, dental treatment, and preoperative procedures. 25,27 However, due to the heterogeneity and limitations of the primary studies, there is currently limited evidence on the effectiveness of virtual reality interventions for relieving pain among children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations